Dietary intake and health risk characterization of cadmium, lead, and mercury in milkfish (Chanos chanos) and tilapia (Oreochromis spp.) from aquaculture farms surrounding Manila bay, Philippines - Kathlene Cleah D. Benitez; Allysa Ross N. Almagro; Patrick David M. Torres; Karl Bryan S. Perelonia; Bryan E. Tanyag; Jerick Jann M. Quiambao; Ulysses M. Montojo (Regulatory Toxicology and Pharmacology, 2026)

Development of an In Vitro Permeation Test Framework For Naloxone Hydrochloride Intranasal Spray: Establishing IVIVR for Bioequivalence Assessment - Tasmin Ara Sultana; Manar Al-Ghabeish; Steven Chopski; Ross Walenga; Diaa Shakleya; Bryan Newman; Muhammad Ashraf; Ahmed Zidan (Pharmaceutical Research, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Regional Nasal Drug Deposition in Pediatric vs. Adult Models: In vitro Insights into User Technique and Breathing Patterns Sensitivity - Mohammad Hejazi; Xiomara Owen; David J. Edwards; Michael Hindle; Worth Longest; Theodore Schuman; Ross Walenga; Steven Chopski; Anubhav Kaviratna; Bryan Newman; Laleh Golshahi (Pharmaceutical Research, 2026)
Purpose Although in vitro studies recommended for establishing bioequivalence of locally acting nasal suspension products provide useful information regarding product performance, currently they are not designed to fully account for variability introduced by patient-specific factors such as administration technique and breathing patterns. This limitation, combined with ethical and practical challenges in conducting pediatric clinical trials, creates a knowledge gap in understanding age-related differences in nasal drug delivery. Methods Anatomically realistic in vitro nasal models representing an average child and adult, in terms of total drug delivery to the sites of intended action posterior to nasal valve, were used to investigate the sensitivity of regional nasal drug deposition to variations in administration parameters and breathing conditions. Three breathing conditions were evaluated: breath hold, gentle sniffing, and vigorous sniffing. Administration parameters were varied using a Box-Behnken experimental design. Results Results showed that for commercially available nasal sprays, breathing patterns did not significantly affect drug delivery in the adult model, but extreme conditions (no breathing vs. vigorous sniffing) caused significant differences in anterior deposition in the child model. Differences between gentle sniffing and the other conditions were not statistically significant. The sensitivity analysis revealed that in vitro drug deposition patterns differ between child and adult nasal cavities under identical user parameter variations, and variable importance differed across nasal cavity regions. Conclusions This study demonstrates the potential for targeted drug delivery by enabling the identification of the optimal administration parameters to achieve desired outcomes, such as enhanced drug deposition in specific nasal regions.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Is this spicy? Investigation of factors that influence spicy food choices by US older adults - Patrycja Urszula Żukowska; Bryan Michael L. Pepito; Helena Maria Andre Bolini; Carolyn F. Ross (Food Quality and Preference, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Transforming the food system: Are farmers ready to take phosphorus stewardship action? - Julia Martin-Ortega; Lukas J. Wolf; Emmanouil Tyllianakis; Aine Anderson; Miller Alonso Camargo-Valero; Dana Cordell; Donnacha G. Doody; Kirsty J. Ross; Brent Jacobs; Shane A. Rothwell; Shervin Shahvi; Erin Sherry; et al. (Environmental Science & Policy, 2024)

In vitro evaluation of intersubject variability in pediatric intranasal drug delivery using nasal spray suspension products - Amir R. Esmaeili; John V. Wilkins; Sana Hosseini; Ali Alfaifi; Mohammad Hejazi; Michael Hindle; Worth Longest; Theodore Schuman; Sneha Dhapare; Anubhav Kaviratna; Ross Walenga; Bryan Newman; et al. (Journal of Aerosol Science, 2024)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Lions and brown bears colonized North America in multiple synchronous waves of dispersal across the Bering Land Bridge - Alexander T. Salis; Sarah C. E. Bray; Michael S. Y. Lee; Holly Heiniger; Ross Barnett; James A. Burns; Vladimir Doronichev; Daryl Fedje; Liubov Golovanova; C. Richard Harington; Bryan Hockett; Pavel Kosintsev; et al. (Molecular Ecology, 2022)
The Bering Land Bridge connecting North America and Eurasia was periodically exposed and inundated by oscillating sea levels during the Pleistocene glacial cycles. This land connection allowed the intermittent dispersal of animals, including humans, between Western Beringia (far northeast Asia) and Eastern Beringia (northwest North America), changing the faunal community composition of both continents. The Pleistocene glacial cycles also had profound impacts on temperature, precipitation and vegetation, impacting faunal community structure and demography. While these palaeoenvironmental impacts have been studied in many large herbivores from Beringia (e.g., bison, mammoths, horses), the Pleistocene population dynamics of the diverse guild of carnivorans present in the region are less well understood, due to their lower abundances. In this study, we analyse mitochondrial genome data from ancient brown bears ( Ursus arctos ; n = 103) and lions ( Panthera spp.; n = 39), two megafaunal carnivorans that dispersed into North America during the Pleistocene. Our results reveal striking synchronicity in the population dynamics of Beringian lions and brown bears, with multiple waves of dispersal across the Bering Land Bridge coinciding with glacial periods of low sea levels, as well as synchronous local extinctions in Eastern Beringia during Marine Isotope Stage 3. The evolutionary histories of these two taxa underline the crucial biogeographical role of the Bering Land Bridge in the distribution, turnover and maintenance of megafaunal populations in North America.

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Inhaled nitric oxide does not improve maximal oxygen consumption in endurance trained and untrained healthy individuals - Andrew R. Brotto; Devin B. Phillips; Victoria L. Meah; Bryan A. Ross; Desi P. Fuhr; Rhys I. Beaudry; Sean van Diepen; Michael K. Stickland (European Journal of Applied Physiology, 2022)

Photothermal Floats for Evaporation Enhancement and Waterfowl Deterrence - Ross Monasmith; Grant Myhre; Jared Geer; Ryan Moe; Bryan Chamba Vasquez; Shyla Allred; Madison Cyr; Emma Wooldridge; Hans Swenson; Stella Capoccia; Dario Prieto Centurion; Courtney Young; et al. (Mine Water and the Environment, 2020)

Ecological niche partitioning within a large predator guild in a nutrient‐limited estuary - Philip Matich; Jerald S. Ault; Ross E. Boucek; David R. Bryan; Kirk R. Gastrich; Christine L. Harvey; Michael R. Heithaus; Jeremy J. Kiszka; Valeria Paz; Jennifer S. Rehage; Adam E. Rosenblatt (Limnology and Oceanography, 2017)
Within oligotrophic ecosystems, resource limitations coupled with interspecific variation in morphology, physiology, and life history traits may lead to niche partitioning among species. How generalist predators partition resources and their mechanisms, however, remain unclear across many ecosystems. We quantified niche partitioning among upper trophic level coastal and estuarine species: American alligators ( Alligator mississippiensis ), bull sharks ( Carcharhinus leucas ), common bottlenose dolphins ( Tursiops truncatus ), common snook ( Centropomus undecimalis ), and Atlantic tarpon ( Megalops atlanticus ) in the Shark River Estuary of the Florida Coastal Everglades, USA using acoustic telemetry, stable isotope analysis, and visual surveys, combined with published diet and life history demographic information. Spatial and isotopic niche overlap occurred among most species, with variability in partitioning among interspecific interactions. However, seasonal variability in habitat use, movements patterns, and trophic interactions may promote coexistence within this resource‐limited estuary. Beyond guild‐level niche partitioning, predators within the Shark River Estuary also exhibit partitioning within species through individual specializations and divergent phenotypes, which may lead to intraspecific variability in niche overlap with other predators. Niche differentiation expressed across multiple organizational levels (i.e., populations and communities) coupled with behavioral plasticity among predators in oligotrophic ecosystems may promote high species diversity despite resource limitations, which may be important when species respond to natural and human‐driven environmental change.

Rapid evolution of sperm length in response to increased temperature in an ectothermic fish - Ross D. Breckels; Bryan D. Neff (Evolutionary Ecology, 2014)

Rapid evolution in response to increased temperature maintains population viability despite genetic erosion in a tropical ectotherm - Ross D. Breckels; Shawn R. Garner; Bryan D. Neff (Evolutionary Ecology, 2014)

Explosive Pleistocene range expansion leads to widespread Amazonian sympatry between robust and gracile capuchin monkeys - Jessica W. Lynch Alfaro; Jean P. Boubli; Link E. Olson; Anthony Di Fiore; Bryan Wilson; Gustavo A. Gutiérrez‐Espeleta; Kenneth L. Chiou; Meredith Schulte; Sarah Neitzel; Vanessa Ross; Doreen Schwochow; Mai T.T. Nguyen; et al. (Journal of Biogeography, 2012)
Aim Capuchin monkey species are widely distributed across Central and South America. Morphological studies consistently divide the clade into robust and gracile forms, which show extensive sympatry in the Amazon Basin. We use genetic data to test whether Miocene or Plio‐Pleistocene processes may explain capuchin species’ present distributions, and consider three possible scenarios to explain widespread sympatry. Location The Neotropics, including the Amazon and Atlantic Coastal Forest. Methods We sequenced the 12S ribosomal RNA and cytochrome b genes from capuchin monkey specimens. The majority were sampled from US museum collections and were wild‐caught individuals of known provenance across their distribution. We applied a Bayesian discrete‐states diffusion model, which reconstructed the most probable history of invasion across nine subregions. We used comparative methods to test for phylogeographic association and dispersal rate variation. Results Capuchins contained two well supported monophyletic clades, the morphologically distinct ‘gracile’ and ‘robust’ groups. The time‐tree analysis estimated a late Miocene divergence between Cebus and Sapajus and a subsequent Plio‐Pleistocene diversification within each of the two clades. Bayesian analysis of phylogeographic diffusion history indicated that the current wide‐ranging sympatry of Cebus and Sapajus across much of the Amazon Basin was the result of a single explosive late Pleistocene invasion of Sapajus from the Atlantic Forest into the Amazon, where Sapajus is now sympatric with gracile capuchins across much of their range. Main conclusions The biogeographic history of capuchins suggests late Miocene geographic isolation of the gracile and robust forms. Each form diversified independently, but during the Pleistocene, the robust Sapajus expanded its range from the Atlantic Forest to the Amazon, where it has now encroached substantially upon what was previously the exclusive range of gracile Cebus . The genus Cebus , as currently recognized, should be split into two genera to reflect the Miocene divergence and two subsequent independent Pliocene radiations: Cebus from the Amazon and Sapajus from the Atlantic Forest.

Genomic analysis of oceanic cyanobacterial myoviruses compared with T4‐like myoviruses from diverse hosts and environments - Matthew B. Sullivan; Katherine H. Huang; Julio C. Ignacio‐Espinoza; Aaron M. Berlin; Libusha Kelly; Peter R. Weigele; Alicia S. DeFrancesco; Suzanne E. Kern; Luke R. Thompson; Sarah Young; Chandri Yandava; Ross Fu; et al. (Environmental Microbiology, 2010)
Summary T4‐like myoviruses are ubiquitous, and their genes are among the most abundant documented in ocean systems. Here we compare 26 T4‐like genomes, including 10 from non‐cyanobacterial myoviruses, and 16 from marine cyanobacterial myoviruses (cyanophages) isolated on diverse Prochlorococcus or Synechococcus hosts. A core genome of 38 virion construction and DNA replication genes was observed in all 26 genomes, with 32 and 25 additional genes shared among the non‐cyanophage and cyanophage subsets, respectively. These hierarchical cores are highly syntenic across the genomes, and sampled to saturation. The 25 cyanophage core genes include six previously described genes with putative functions ( psbA , mazG , phoH , hsp20 , hli03 , cobS ), a hypothetical protein with a potential phytanoyl‐CoA dioxygenase domain, two virion structural genes, and 16 hypothetical genes. Beyond previously described cyanophage‐encoded photosynthesis and phosphate stress genes, we observed core genes that may play a role in nitrogen metabolism during infection through modulation of 2‐oxoglutarate. Patterns among non‐core genes that may drive niche diversification revealed that phosphorus‐related gene content reflects source waters rather than host strain used for isolation, and that carbon metabolism genes appear associated with putative mobile elements. As well, phages isolated on Synechococcus had higher genome‐wide %G+C and often contained different gene subsets (e.g. petE , zwf , gnd , prnA , cpeT ) than those isolated on Prochlorococcus . However, no clear diagnostic genes emerged to distinguish these phage groups, suggesting blurred boundaries possibly due to cross‐infection. Finally, genome‐wide comparisons of both diverse and closely related, co‐isolated genomes provide a locus‐to‐locus variability metric that will prove valuable for interpreting metagenomic data sets.

Pollution-induced behavioural effects in the brown bullhead (Ameiurus nebulosus) - Ross D. Breckels; Bryan D. Neff (Ecotoxicology, 2010)